EKSTRASI DEDAK PADI SEBAGAI PENGAYAAN SUMBER MAKANAN BERPROTEIN TINGGI DI SUMATERA BARAT - Sari, Santi Amelia; Putri, Restika; Suparmin, Suparmin; Astuti, Widya (Program Kreativitas Mahasiswa - Penelitian, 2014)
West Sumatra is an area that still has a high poverty rate is as much as 407,470 people or 8.14% of the total population. One of the effect of this situation is approximately 0.9% of West Sumatra children still suffer from malnutrition due to lack of nutrition, especially protein. By extracting the rice bran, will be acquired proteins that can be used to ensure adequate intake of proteins which have not fulfilled. Itâs caused by soybean price instability which has been used as a source of protein for most of the population of West Sumatra. By varying the alkaline solution, pH and extraction time will be obtained optimum conditions to obtain the highest protein concentrate that can be used as an alternative protein source. For the determination of protein content contained in each sample was used Kjeldahl method. Having done this research, was obtained the optimum conditions is KOH solution with extraction time was 3 hours and pH 10. Based on the results of ANOVA test shows that the extraction time and extraction pH have significant effect on the yield of concentrate protein. But, extraction solution factor didnât have significant effect.Keywords: Extraction, Rice bran, Enrichment, Sources of food, High protein